Pengaruh Modal Kerja Terhadap Profitabilitas Perusahaan Perdagangan Eceran di Bursa Efek Indonesia - Refni Sukmadewi (Komunitas Dosen Indonesia, 2020)
The purpose of this study is to determine the effect of working capital management which consists of: Cash Turnover, Accounts Receivable Turnover and Inventory Turnover on the level of profitability in retail trading companies listed on the Indonesia Stock Exchange in 2017-2019. This research uses quantitative research by observing and studying audited financial reports from retail trading companies listed on the Indonesia Stock Exchange during the study period. The analysis method used is multiple regression analysis. The sample of this study amounted to 14 companies. The results of this study indicate that partially working capital management which consists of: Cash Turnover has a positive effect on Profitability, Receivables Turnover has a positive effect on Profitability and Inventory Turnover has a positive and significant effect on profitability in retail trading companies listed on the Indonesia Stock Exchange 2017-2019. Furthermore, simultaneously working capital management which consists of: Cash Turnover, Accounts Receivable Turnover and Inventory Turnover affect the profitability of 2017-2019 companies listed on the Indonesia Stock Exchange 2017-2019. Keywords: Cash Turnover, Accounts Receivable Turnover, Inventory Turnover, Working Capital, Profitability